Kecerdasan Emosional san Agrasivitas pada Remaja - I Nengah Sumirta (Jurnal Gema Keperawatan, 2013)
This research aim to determine the relationship between emotional intelligence and aggressiveness in adolescents. This design use the analysis research design with cross-sectional approach using cluster sampling and proportional random sampling. The population number wash 594 and the sample is 185 respondents. The results of data analysis with rank spearman non parametrict test found the r value -0,776 and p value of 0,000, this suggest, the research hypothesis wich states “there is a significant association between emotional intelligence and aggressiveness of adolescences.